Guillain Barre Syndrome in the elderly: Experience from a tertiary-care hospital in India. (December 2017) - Nagappa, M.; Rahul, W.; Sinha, S.; Bindu, P.S.; Mathuranath, P.S.; Rao, S.; Periyavan, S.; Umamaheshwara Rao, G.S.; Taly, A.B.
Highlights: Advanced age is a marker for greater severity and poor recovery in Guillain Barre Syndrome. Elderly have longer interval between antecedent infection and onset of Guillain Barre Syndrome. Elderly have shorter symptom duration, greater disease severity and longer time to recovery. Elderly have higher incidence of facial palsy and requirement for mechanical ventilation. Significant functional recovery occurs in majority of elderly with Guillain Barre Syndrome with intensive supervised care. Abstract: Age influences incidence and prognosis of Guillain Barre Syndrome (GBS), common cause of ascending areflexic quadriparesis. Dedicated studies on elderly GBS are infrequent. This study aimed to describe clinical features and outcome at hospital-discharge in patients aged ≥ 60 years with GBS. Medical records of 70 elderly GBS over 15 years were analysed. Mean symptom-duration was 5.78 ± 4.5 days and onset-to-peak 5.14 ± 4.4 days. Antecedent events preceded GBS by 8.07 ± 9.9 days and included: fever (n = 19), respiratory infection (n = 6), and gastroenteritis (n = 5). Clinical features were weakness of facial (n = 34), bulbar (n = 13), extraocular (n = 4) and respiratory (n = 20) muscles and recurrence (n = 4). Nine had Hughes disability score (HDS) of three or less. Sensory symptoms and signs included paresthesias (n = 40), pain (n = 24), and impaired kinaesthetic sensation (n = 14). Laboratory abnormalities included albumino-cytological dissociation (n = 50), hyponatremia (n = 36) and elevated creatine kinase (n = 18). Electrophysiological subtypes were: primary demyelinating (n = 52), inexcitable (n = 3), equivocal (n = 2) and axonal (n = 1). Fifty-seven patients treated with plasmapheresis (n = 48) or intravenous immunoglobulin (n = 9) had mean HDS of 3.53 ± 0.7 at discharge. Twenty-one were ambulant (HDS ≥ 3), one had persisting respiratory weakness and one died. Striking differences between the 'elderly' and 100 'adults' seen over 20 months were shorter symptom-duration, higher frequency of facial palsy and hyponatremia, lower frequency of pain, lower mean MRC sum score and worse HDS at study-entry and discharge (p < 0.05). Requirement for mechanical ventilation and cardiac autonomic dysfunction was higher among elderly (p:0.02). In conclusion, in this cohort of elderly GBS, there was a higher frequency severe GBS and demyelinating electrophysiology.